1.4-3=2+h

Simple and best practice solution for 1.4-3=2+h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1.4-3=2+h equation:


Simplifying
1.4 + -3 = 2 + h

Combine like terms: 1.4 + -3 = -1.6
-1.6 = 2 + h

Solving
-1.6 = 2 + h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-1h' to each side of the equation.
-1.6 + -1h = 2 + h + -1h

Combine like terms: h + -1h = 0
-1.6 + -1h = 2 + 0
-1.6 + -1h = 2

Add '1.6' to each side of the equation.
-1.6 + 1.6 + -1h = 2 + 1.6

Combine like terms: -1.6 + 1.6 = 0.0
0.0 + -1h = 2 + 1.6
-1h = 2 + 1.6

Combine like terms: 2 + 1.6 = 3.6
-1h = 3.6

Divide each side by '-1'.
h = -3.6

Simplifying
h = -3.6

See similar equations:

| x^4+2x+2=0 | | 0.3(k-0.2)=0.6 | | 5x^2-4x-2=0 | | 12+3x=x | | 8x^3+6x^2-5x+1=0 | | 140-7x=29x+16 | | 2x-9=x | | -3x-1-5x+4= | | t^2=3t+7 | | 9-7x=108-28x | | 9-2x=x | | 6+5x=x | | x-2(x-1)=4-3(x-2) | | 13-8z=7 | | 12+5=11+12x | | -3(x-7)+2= | | 9(2-a)=63 | | 3(2+5m)=-54 | | 17(x-2)=34 | | 17(x-2)= | | 10-2(x+3)=3+3(2x+5) | | 4b-(9b-8)= | | 3x^2+10x+5=0 | | 379.94=3.14*r^2 | | 4+45=8x+13 | | 2x-5x=x+8 | | 4x+10=2x+29 | | -7y-(2y+4)= | | 4x^2+13=3 | | 2x^2=162 | | 5-4(x+1)=4x-3(4x-1)-4 | | 9+3b=18 |

Equations solver categories